The Effect of Diabetes Gymnastics on Blood Sugar Levels Diabetes Mellitus Patients at the Indonesian Diabetes Association Clinic Diabetes Indonesia (PERSADIA) Tulungagung: Pengaruh Senam Diabetes Terhadap Kadar Gula Darah Pasien Diabetes Mellitus di Klinik Persatuan Diabetes Indonesia (PERSADIA) Tulungagung - Sagita, Denindar Richa; Lasman; Suharyoto, Suharyoto; Rohmawati, Indah (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2024)
Diabetes mellitus (DM) is a group of heterogeneous disorders characterized by the increase content of glucose in the blood or hyperglycemia. One of the recommended physical exercises is diabetes gymnastics. Gymnastics diabetes is a physical gymnastics according to age and physical status. This research purpose to find the effect of diabetes gymnastics on blood sugar content of DM patients at PERSADIA Tulungagung clinic. The research design is Quasi Experimental design with one-group pretest - posttest design. Technique sampling is quota sampling, the population is all patient of diabetes mellitus PERSADIA at December 2016 are 125 patients, the sampel are 30 respondents members of PERSADIA. The independent variable is diabetic gymnastic and dependent variable is blood glucose. Respondents were given gymnastics 1x, duration 30-40 minutes. Data collection tool is a questionnaire about the characteristics of respondents and observations to check the blood sugar before and after exercise. Then data processing by editing, coding, scoring and tabulating. Then the data were analyzed using Paired t Test. The research was conducted on April 22, 2017 and April 29, 2017. The result showed that the average blood sugar level before the diabetes gymnastics intervention was 248,20 mg/dl while on average of blood sugar level after diabetes gymnastics intervention was 247,90 mg/dl. Ρ value = 0.037 which means there is an effect of diabetes gymnastics on blood sugar content to diabetes mellitus patient at PERSADIA Tulungagung Clinic. The results showed that diabetic gymnastics is proven to reduce blood sugar content of diabetes mellitus patient because physical exercise leads to an increase in blood flow, capillary mesh more open so that more insulin receptors that affect the decrease in blood sugar.